1998
DOI: 10.1016/s1010-7940(98)00123-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve operation via Port Access versus median sternotomy

Abstract: Objective: The advantages and disadvantages of minimally invasive Port Access mitral valve operation have not been defined relative to standard median sternotomy. A study was therefore designed to delineate differences in outcome from mitral operation via Port Access versus sternotomy in comparable patients. Methods: The records of 41 consecutive patients undergoing isolated mitral valve replacement (n = 14) or repair (n = 27) were examined. All operations were performed using cardioplegic arrest through eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 7 publications
2
100
0
Order By: Relevance
“…These observations have also been reported in less invasive valve operations performed by the group at New York University (New York, NY) [11]. Glower [12] at Duke University (Durham, NC) reports that patient recovery with the small thoracotomy approach continues to progress more rapidly there as well.…”
Section: Clinical Resultssupporting
confidence: 52%
“…These observations have also been reported in less invasive valve operations performed by the group at New York University (New York, NY) [11]. Glower [12] at Duke University (Durham, NC) reports that patient recovery with the small thoracotomy approach continues to progress more rapidly there as well.…”
Section: Clinical Resultssupporting
confidence: 52%
“…In these smaller randomized trials, adverse cardiac and cerebrovascular events as well as operative mortality were found to be comparable between the RT and MS groups [17][18][19]. In unmatched studies, RT also had advantages of earlier return to normal activity [20], less reoperation for bleeding [6], decreased pain [3], but increased risk of aortic dissection [5], while other unmatched studies found little effect of the RT approach on outcomes [21,22].…”
Section: Commentmentioning
confidence: 93%
“…A number of studies, including meta-analyses, documented reductions in the duration of mechanical ventilation when minimally invasive approaches were utilized (8,10,12,13,19,20,25,26). Yet other experienced centers have not shown such a …”
Section: Comparison To Sternotomy Approachmentioning
confidence: 99%
“…When 22 patients who underwent reoperative mitral valve surgery via minithoracotomy after previous median sternotomy were interviewed, they all felt their recovery was more rapid and less painful than after their original sternotomy (32). Finally, one experienced center documented that patients return to normal activity five weeks earlier after thoracoscopy-assisted mitral valve surgery than after a median sternotomy (26). P r o c e d u r a l c o s t a n d r e s o u r c e u t i l i z a t i o n a r e increasingly important factors in evaluating different treatments.…”
mentioning
confidence: 99%